(untitled) (diségno, 2021)
Imagining and creating new worlds has always been one of the deepest desires of mankind. Today as yesterday, the insatiable hunger of the creative genius characterizes the poietic activity of certain artists and architects who see the world in an imaginative way in order to give birth to original pieces of reality (or unreality). Reason and imagination freely interact in the artistic mind, decomposing and recomposing fragments of architectures, urban and natural landscapes to build new visions. The history of art is full of examples of visionary artists whose production was mainly devoted to the visionary representation of places such as the Baroque scenic designs by the Galli da Bibiena dynasty, the imaginary views by Piranesi and the masters of capriccio as well as the futuristic visions of Sant’Elia and Chernikhov. Similar experimentations can be found today in the work of environment concept artists operating in the entertainment industry: these artists create depictions of fictional universes characterized by an extraordinary evocative power, in which reality and imagination coexist. These contemporary visionaries can see beyond the visible, drawing from memory and fantasy, providing coherent and incredibly realistic pictures of imaginary places, to the point that they appear possible in the eyes of the spectator.